A Versatile In‐Situ Electron Paramagnetic Resonance Spectro‐electrochemical Approach for Electrocatalyst Research. Issue 22 (14th October 2020) - Neukermans, Sander; Samanipour, Mohammad; Vincent Ching, H. Y.; Hereijgers, Jonas; Van Doorslaer, Sabine; Hubin, Annick; Breugelmans, Tom
Abstract: Empirical electrocatalyst research generally consists of the synthesis and experimental characterization of catalysts and the analysis of electrolysis products by conventional analytical techniques. In‐situ electron paramagnetic resonance spectro‐electrochemistry provides an evidence‐based in‐depth understanding of the formed intermediates and the reaction mechanism enabling the desired tuning of electrocatalysts. The use of this technique has been underexploited because of the opposite requirements they impose on the conventional setup. In this work, a versatile electrode with commercially available indium tin oxide on polyethylene terephthalate (PET) was constructed for the first time which can fit inside commonly used flat cells. It allows reproducible electrodeposition of catalytic material combined with sensitive radical detection, owing to its large surface area and minimal disruption to the resonator's Q‐factor. Moreover, with a resistivity of 8–10 Ω sq −1, the surface potential of the thin semiconductor electrode within the resonator was well‐controlled, allowing targeted radical production. Abstract : A novel electrode design for combined in‐situ electrochemical electron paramagnetic resonance experiments is presented. The use of a transparent Indium Tin Oxide on PET semiconductor as a substrate for electrocatalyst deposition and in‐situ investigation of radical intermediates provides unique opportunities in catalyst research. The electrode approaches the maximum available surface area in the electrolytic flat cell resulting in superior sensitivity.